Ocular Surface Changes Associated with Face Masks in Healthcare Personnel during COVID-19 Pandemic - Filippo Tatti; Lorenzo Mangoni; Simone Pirodda; Giuseppe Demarinis; Claudio Iovino; Emanuele Siotto Pintor; Germano Orrù; Luigi Isaia Lecca; Marcello Campagna; Gloria Denotti; Enrico Peiretti (Life, 2022)
The aim of this study was to investigate ocular surface changes associated with face mask (FMs) use of healthcare personnel during the COVID-19 pandemic. We prospectively evaluated 200 eyes of 100 individuals during working hours and 40 eyes of 20 individuals during their rest days as a control group. Dry eye symptoms were assessed with the Ocular Surface Disease Index (OSDI) and McMonnies questionnaire. The clinical investigation included the best corrected visual acuity (BCVA), corneal fluorescein staining (FS), break-up time (BUT), and Schirmer test I before and after a 7-h work shift with a continuative use of surgical or N95 masks. The control group was evaluated similarly twice a day, at 8:00 a.m. and at 3:00 p.m.. In the study group, BCVA, FS, BUT, and Schirmer test were investigated and there was a significant negative variation at the end of the shift. On the contrary, the control group did not show significant variations of any clinical feature. Furthermore, no significant changes in clinical parameters were observed during the use of surgical or N95 masks. In conclusion, FMs continuative use resulted in daily ocular surface modifications specifically in healthcare personnel.